Inflammatory Bowel Disease-Associated Gut Commensals Degrade Components of the Extracellular Matrix - Ana Maria Porras; Hao Zhou; Qiaojuan Shi; Xieyue Xiao; Randy Longman; Ilana Lauren Brito (mBio, 2022)
ABSTRACT Extracellular matrix (ECM) remodeling has emerged as a key feature of inflammatory bowel disease (IBD), and ECM fragments have been proposed as markers of clinical disease severity. Recent studies report increased protease activity in the gut microbiota of IBD patients. Nonetheless, the relationship between gut microbiota and ECM remodeling has remained unexplored. We hypothesized that members of the human gut microbiome could degrade the host ECM and that bacteria-driven remodeling, in turn, could enhance colonic inflammation. Through a variety of in vitro assays, we first confirmed that multiple bacterial species found in the human gut are capable of degrading specific ECM components. Clinical stool samples obtained from ulcerative colitis patients also exhibited higher levels of proteolytic activity in vitro, compared to those of their healthy counterparts. Furthermore, culture supernatants from bacteria species that are capable of degrading human ECM accelerated inflammation in dextran sodium sulfate (DSS)-induced colitis. Finally, we identified several of the bacterial proteases and carbohydrate degrading enzymes (CAZymes) that are potentially responsible for ECM degradation in vitro. Some of these protease families and CAZymes were also found in increased abundance in a metagenomic cohort of IBD. These results demonstrate that some commensal bacteria in the gut are indeed capable of degrading components of human ECM in vitro and suggest that this proteolytic activity may be involved in the progression of IBD. A better understanding of the relationship between nonpathogenic gut microbes, host ECM, and inflammation could be crucial to elucidating some of the mechanisms underlying host-bacteria interactions in IBD and beyond. IMPORTANCE Healthy gut epithelial cells form a barrier that keeps bacteria and other substances from entering the blood or tissues of the body. Those cells sit on scaffolding that maintains the structure of the gut and informs our immune system about the integrity of this barrier. In patients with inflammatory bowel disease (IBD), breaks are formed in this cellular barrier, and bacteria gain access to the underlying tissue and scaffolding. In our study, we discovered that bacteria that normally reside in the gut can modify and disassemble the underlying scaffolding. Additionally, we discovered that changes to this scaffolding affect the onset of IBD in mouse models of colitis as well as the abilities of these mice to recover. We propose that this new information will reveal how breaks in the gut wall lead to IBD and will open up new avenues by which to treat patients with IBD.